PENINGKATANÃÂ PEMAHAMANÃÂ PROSESÃÂ PENYEARAHANÃÂ ARUSÃÂ PADAÃÂ SISTEMÃÂ PENGISIANÃÂ DENGANÃÂ MENGGUNAKANÃÂ ALATÃÂ PERAGAÃÂ SISTEMÃÂ PENGISIANÃÂ - Wahid, Fathu RahmanÃƒÂ‚Ã‚Â ; WidjanarkoÃƒÂ‚Ã‚Â , DwiÃƒÂ‚Ã‚Â ; RusiyantoÃƒÂ‚Ã‚Â , - (Jurnal Pendidikan Teknik Mesin, 2008)
PenelitianÃÂ  iniÃÂ  bertujuanÃÂ  untukÃÂ meningkatkanÃÂ  pemahamanÃÂ mahasiswaÃÂ  tentangÃÂ  penyearahanÃÂ arusÃÂ  pada sistemÃÂ pengisianÃÂ otomotifÃÂ denganÃÂ menggunakanÃÂ alataÃÂ peragaÃÂ sistemÃÂ pengisian.ÃÂ PopulasiÃÂ penelitianÃÂ adalahÃÂ mahasiswaÃÂ teknikÃÂ mesinÃÂ yangÃÂ mengambilÃÂ mataÃÂ kuliahÃÂ sistemÃÂ kelistrikanÃÂ otomotifÃÂ denganÃÂ sampelÃÂ berjumlahÃÂ 30ÃÂ orang.DesainÃÂ penelitianÃÂ adalahÃÂ quasiÃÂ experimentÃÂ denganÃÂ perlakuanÃÂ tambahanÃÂ padaÃÂ aktifitasÃÂ belajar.ÃÂ DataÃÂ diperolehÃÂ denganÃÂ pretesÃÂ (sebelumÃÂ penerapanÃÂ alatÃÂ peragaÃÂ sistemÃÂ pengisian)ÃÂ danÃÂ posÃÂ  tesÃÂ (setelahÃÂ penerapanÃÂ alatÃÂ peragaÃÂ sistem pengisian).ÃÂ DataÃÂ  selanjutnyaÃÂ  dibandingkan.ÃÂ HasilÃÂ  penelitianÃÂ menunjukkanÃÂ  bahwaÃÂ  pemehamanÃÂ mahasiswaÃÂ  dalam penyearahanÃÂ arusÃÂ padaÃÂ sistemÃÂ pengisianÃÂ otomotifÃÂ meningkatÃÂ secaraÃÂ signifikanÃÂ denganÃÂ penggunaanÃÂ alatÃÂ peragaÃÂ sistemÃÂ pengisian. ÃÂ  KataÃÂ kunci:ÃÂ alatÃÂ peragaÃÂ penyearahanÃÂ arus,ÃÂ sistemÃÂ pengisianÃÂ ÃÂ ThisÃÂ researchÃÂ wasÃÂ conductedÃÂ toÃÂ improveÃÂ studentsÃ¢â¬â¢ÃÂ understandingÃÂ onÃÂ directingÃÂ theÃÂ currentÃÂ inÃÂ automotiveÃÂ chargingÃÂ systemÃÂ byÃÂ applyingÃÂ itsÃÂ teachingÃÂ aid.ÃÂ TheÃÂ populationÃÂ wasÃÂ mechanicalÃÂ engineeringÃÂ studentsÃÂ programmingÃÂ automotiveÃÂ electricalÃÂ systemÃÂ subjectÃÂ andÃÂ 30ÃÂ studentsÃÂ participatedÃÂ asÃÂ sample.ÃÂ ThisÃÂ researchÃÂ wasÃÂ aÃÂ timeÃÂ seriesÃÂ designÃÂ quasiÃÂ experimentÃÂ researchÃÂ carriedÃÂ outÃÂ byÃÂ givingÃÂ additionalÃÂ treatmen inÃÂ  learningÃÂ activities. DataÃÂ wasÃÂ collectedÃÂ byÃÂ pretestÃÂ (beforeÃÂ applyingÃÂ chargingÃÂ systemÃÂ teachingÃÂ aid)ÃÂ andÃÂ postÃ¢â¬ÂtestÃÂ (afterÃÂ applyingÃÂ chargingÃÂ systemÃÂ teachingÃÂ aid).ÃÂ TheÃÂ dataÃÂ wasÃÂ thenÃÂ compared.ÃÂ TheÃÂ resultÃÂ indicatedÃÂ thatÃÂ theÃÂ studentsÃ¢â¬â¢ÃÂ  understandingÃÂ  onÃÂ  directingÃÂ  theÃÂ  currentÃÂ  inÃÂ automotiveÃÂ chargingÃÂ systemÃÂ significantlyÃÂ increasedÃÂ dueÃÂ toÃÂ applyingÃÂ chargingÃÂ systemÃÂ teachingÃÂ aid. ÃÂ  Keywords:ÃÂ directÃÂ current,ÃÂ teachingÃÂ aid,ÃÂ chargingÃÂ system